Controlling And Monitoring Of Vegetables Growth With Smart Greenbox Automation System Using Machine Learning - Wijaya, Nigo Wisnu; Karna, Nyoman Bogi Aditya; Irawan, Arif Indra (eProceedings of Engineering, 2023)
Currently, agricultural technology is one of thetechnologies that help many people to solve their daily problemsor activity. People on the city areas are farming in their houseand they usually can’t control their plants properly because oftheir busyness. However, the technology of Agricultural alwaysdeveloping in terms of creating ideal ways and condition for acrop. The presence of Internet of Things (IoT) technology hasbecome a major break through for societal issues. IoT canmakes people easier in controlling and monitoring their cropsanywhere and anytime with remote. Greenbox is a tool whichcan contain several plants that we can monitor and control theirgrowth. The data that will be displayed on the website is the datataken by the sensor on the greenbox device, which is stored inthe firebase database, then the user will carry out commandsaccording to the database. Sensors are used to determine thevalue of plant growth parameters. The expectation of thisresearch is that the output of the system built can be a solutionto problems that exist in the community so that the prototypesthat are built can be perfected and marketed to the public.Keyword— Greenbox, Internet of Things, Firebase